Analgesic effects of gabapentin and ibuprofen on the pain in post therapy of root canal; a randomized double-blind clinical trial - Abbas Mesgarani; Sina Mirzaeerad; Ali Akbar Moghadamnia; Mona Mahyar; Arash Poorsattar Bejeh Mir; Maryam Ehsani (Babol University of Medical Sciences, 2014)
Introduction: Inhibiting the pain which affects both the patients and dentists is an important factor during treating dental patients. The aim of this study was to assess the analgesic effect of two medications ibuprofen and gabapentin on the post-endodontic-therapy pain. Methods: Forty patients who need root canal therapy with Visual Analog Scale (VAS)>40, participated in this double-blind randomized clinical trial study and randomly divided into two groups. The ibuprofen group received 800 mg ibuprofen 1 hour before the treatment and 400 mg at 6, 12 and 24 hours after the treatment procedure, and the other group received 600 mg gabapentin 1 hour before the treatment and 300 mg at 6, 12 and 24 hours after treatment. Patients recorded the intensity of pain via VAS before treatment and every hour for the first 6 h after taking the medication and then every 6 h thereafter for a total of the 48-hour period. (Two tablets of acetaminophen codeine (325mg/20mg) were given to the patients as a rescue dose. Results: The analgesic effect of gabapentin was significantly higher than ibuprofen in 12h (p=0.035), 24h (p<0.001), and 48 h (p=0.012) after analgesic intake. It has been also shown that both medicines had analgesic effect significantly. (p<0.0001) Conclusions: Gabapentin had greater analgesic effects on the sample group from 12 h until 48h after taking in comparison with ibuprofen so it seems that it could be an appropriate option for postoperative pain inhibition.